Excimer laser technology in percutaneous coronary interventions: Cardiovascular laser society's position paper. (1st March 2022) - Golino, L.; Caiazzo, G.; Calabrò, P.; Colombo, A.; Contarini, M.; Fedele, F.; Gabrielli, G.; Galassi, A.R.; Golino, P.; Scotto di Uccio, F.; Tarantini, G.; Argentino, V.; et al.
Abstract: Excimer Laser Coronary Atherectomy (ELCA) is a well-established therapy that emerged for the treatment of peripheral vascular atherosclerosis in the late 1980s, at a time when catheters and materials were rudimentary and associated with the most serious complications. Refinements in catheter technology and the introduction of improved laser techniques have led to their effective use for the treatment of a wide spectrum of complex coronary lesions, such as thrombotic lesions, severe calcific lesions, non-crossable or non-expandable lesions, chronic occlusions, and stent under-expansion. The gradual introduction of high-energy strategies combined with the contrast infusion technique has enabled us to treat an increasing number of complex cases with a low rate of periprocedural complications. Currently, the use of the ELCA has also been demonstrated to be effective in acute coronary syndrome (ACS), especially in the context of large thrombotic lesions. Highlights: The ELCA procedure has become an established therapy for the treatment of a wide range of coronary lesions. The ELCA treatment helps to complete uncrossable and undilatable coronary lesions, stent under-expansion, hard CTO cases. The ELCA technique is also very useful in ACS, especially in cases in which intracoronary thrombotic burden is predominant. The 0.9 mm ELCA-X80 catheters requires only a typical 0.014 guidewire, and have the potential to treat any type of calcified lesion. The use of high energy pulse (80 flunce / 80 repetition rate) associated to contrast injection (Explosion Technique) is crucial in complex cases.